A Library in the Grands Moulins de Paris: challenging Reality - Tresson, Catherine (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2006)
In 2006, the University of Paris 7 and its new Main Library will move to Paris Rive Gauche, a recently developed neighbourhood on the left bank of the Seine. The library will occupy most of the city’s former industrial mills, the Grands Moulins de Paris. As part of the project, the library developed a very detailed functional program. The facilities are expected to comprise 1,800 workstations (half of which will be computerized), and upon completion will have a capacity of 300,000 freely accessible documents and 350,000 documents in store over a total surface area of some 12,000 m2. The architect Rudy Ricciotti won the international competition to design the library held in 2001. Perfectly suited to its function, the industrial building in which the library is housed dates from the 1920s. It presents both advantages (vast surfaces, sufficient load-bearing capacity, natural light, etc.) and obstacles (restrictions on free circulation, forests of columns in certain areas, interrupted spaces, etc.) to being transformed into a library that is functional and adapted to its purposes. The building’s structure and the constraints it imposed profoundly influenced the program which had to be adjusted, and also affected other aspects, including the arrangement and features of the furnishings as well as the building’s system of signs. In agreement with the university, the library worked in close collaboration with the architect from the earliest sketches onwards. As a result, his initial plan also evolved considerably. The installation of the library in the Grands Moulins offers us a chance to observe the nature and effects of the interactions between the transformation of a building and the evolution of a program.